2018
DOI: 10.5137/1019-5149.jtn.24429-18.2
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and interrelationship of concomitant anomalies in congenital scoliosis

Abstract: Maternal diabetes mellitus, hypoxia, vitamin deficiencies, and anticonvulsant medication use have been associated with CS (9). Development of the spinal cord and organs of mesodermal origin is closely related to development of the vertebral column (1). As a result, CS is often associated with anomalies of the spinal cord, cardiovascular system, and genitourinary system (12). Previously, the incidences of intraspinal and other organ system pathologies associated with CS were reported █ INTRODUCTION C ongenital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
4
9
2
Order By: Relevance
“…Faloon et al [31] concluded that there was no difference between males and females in the proportion of adolescent idiopathic scoliosis cases with neuraxial abnormalities. Sevencan et al [16] reported that in CS patients, females had a significantly higher incidence of intraspinal abnormalities than males. In the present study, we concluded that the incidence of intraspinal abnormalities in males and females were 30% and 41%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Faloon et al [31] concluded that there was no difference between males and females in the proportion of adolescent idiopathic scoliosis cases with neuraxial abnormalities. Sevencan et al [16] reported that in CS patients, females had a significantly higher incidence of intraspinal abnormalities than males. In the present study, we concluded that the incidence of intraspinal abnormalities in males and females were 30% and 41%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1. A total of 10 studies published from 2001 to 2019 described intraspinal abnormalities in CS patients undergoing MRI examinations [1,16,[19][20][21][22][23][24][25]28]. The basic characteristics of the included studies are shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations